‘SI VIVARIIS INCLUSAE FERAE’… STATUS PRAWNY DZIKICH ZWIERZĄT ŻYJĄCYCH W ‘VIVARIA’ I PARKACH MYŚLIWSKICH W PRAWIE RZYMSKIM - Benincasa, Zuzanna (Zeszyty Prawnicze, 2016)
‘SI VIVARIIS INCLUSAE FERAE’: THE STATUS IN ROMAN LAW OF WILD ANIMALS KEPT IN ‘VIVARIA’ AND GAME PARKS Summary The paper discusses the legal questions concerning the keeping and rearing of wild animals in game reserves and game parks (vivaria) by Roman landowners. According to the fundamental principle of ius gentium a wild animal was no-one’s property (res nullius) and could be captured by anyone, who then became its owner, regardless of whether the animal was captured on their own or another person’s property. Property owners who established enclosed game reserves near their villas for wild animals such as boars, deer, birds and fish held the exclusive right to hunt the animals on their reserve and enjoy the profit from them, as the animals confined on their property were considered theirs by law. Originally vivaria were small and catered mainly for the needs of the family. As Roman society became more and more affluent vivaria were transformed into large reserves where landowners kept and bred various species of domestic and exotic animals, not only for profit from selling them in the market but also for their own pleasure and to manifest their social status (delectationis causa). Since hunting became a noble sport among upper-class Romans, even huge forest areas were enclosed (therotrophium). According to the literary evidence, by the late Republic profit from vivaria had become a considerable source of revenue for landowners, so Roman jurisprudence had to take the phenomenon into consideration in discussions of various issues related to land management. Roman jurists focused first of all on who owned animals kept in game reserves and game parks: as Paul observed in D. 41,2,3,14 only animals which had been captured and enclosed in a vivarium by the landowner were considered his property, while animals living in the wild (in silvis circumseptis) were still no-one’s property. The other question raised by Roman jurists concerned the usufruct of a vivarium i.e. the way in which the usufructuary could farm the profit and benefits accruing from a game reserve (num exercere eas fructuarius possit, occidere non possit). This problem was resolved by applying an analogical principle to the usufruct of vivaria as for the usufruct of a herd of domestic animals (grex). This solution resolved disputes over who owned a single animal enclosed in a vivarium, and also gave the usufructuary a discretional right to enjoy of a vivarium, while at the same time not putting its owner at risk. The other issue discussed by Roman jurists in the context of game reserves and game parks was whether wild animals and the profit accruing from hunting them should be deemed a fructus fundi.